AB0150 Increased eryptosis levels in primary antiphospholipid syndrome patients. (15th June 2017) - Vomero, M; Ceccarelli, F; Finucci, A; Pensa, C; Barbati, C; Colasanti, T; Spinelli, FR; Massaro, L; Truglia, S; Perricone, C; Miranda, F; Mauro, FR; et al.
Abstract : Background: Erythrocytes (RBCs) hold a crucial role in hemostasis and their integrity is influenced by different stimuli including circulating inflammatory mediators. Even though RBCs do not have nuclei and mitochondria, they have developed a process allowing them to undergo a rapid self-destruction named eryptosis. The exact mechanism of erythrocytes cell death is not fully clarified yet but it seems to involve Ca 2+ and ceramide formation, leading to cell shrinkage and externalization of phosphatidylserine (PS) (1). Interaction between platelets and erythrocytes could participate in an increasing risk of thrombotic episodes typical of several diseases including antiphospholipid syndrome (APS). In fact, not only signals triggering eryptosis are involved in thrombosis activation, but also recent studies have demonstrated how PS-exposing erythrocytes are able to adhere to the vascular wall causing an impairment of circulation (2, 3). Objectives: Enhanced eryptosis is known to contribute to several pathological conditions (1) but the involvement of this process in APS has not been investigated yet. For this reason the aim of the study was to evaluate eryptosis levels in APS, healthy subjects positive for antiphospolipid antibodies without clinical manifestations (aPL carriers), autoimmune haemolytic anaemia (AIHA) and healthy donors (HD). Methods: 27 patients with primary APS (M/F 5/22, mean age 51.1±7.6 years), 14 aPL carriers (M/F 3/11, mean age 48.9±8.4 years) were recruited after written informed consent. Moreover 10 AIHA patients and 12 HD were also enrolled as positive and negative control group respectively. RBCs were isolated from whole blood after centrifugation and eryptosis levels were analysed by flow cytometry, evaluating the percentage of annexin V-positive cells (PS-exposing cells). Flow cytometry was also use to estimated cellular volume from forward scatter (FSC). Results: APS patients showed higher levels of eryptosis compared to HD (p=0.01). Interestingly, the percentage of annexin V-positive RBCs was lower in aPL carriers respect to APS patients (p=0.001). Moreover, an inverse correlation between RBCs volume and eryptosis was found in APS patients (r=-0.4, p=0.03). No clinical correlation between eryptosis and clinical manifestations were noticed. As expected, eryptosis was upregulated in AIHA patients compared to all populations studied (p<0.0001). Conclusions: Our study provides for the first time evidence of eryptosis enhancement in APS patients suggesting a possible contribution of RBCs apoptosis in the pathogenesis of the disease. References: Lang E, Lang F. Triggers, inhibitors, mechanisms, and significance of eryptosis: the suicidal erythrocyte death. Biomed Res Int. 2015;2015:513518. Borst O, Abed M, Alesutan I, Towhid ST, Qadri SM, Foller M, Gawaz M, Lang F. Dynamic adhesion of eryptotic erythrocytes to endothelial cells via CXCL16/SR-PSOX. Am J Physiol Cell Physiol. 2012;302:C644-C651. Pretorius E, du Plooy JN, Bester J. A Comprehensive Review on Eryptosis. Cell Physiol Biochem. 2016;39:1977–2000. Disclosure of Interest: None declared